ANALISIS PENDEKATAN DEEP LEARNING DALAM KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN IPAS SISWA KELAS V SDN SIDOREJO 02 - Budi Pinilih, Danu; Meidawati Suswandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the use of the Deep Learning approach in IPAS (Integrated Science and Social Studies) learning to enhance the critical thinking skills of fifth-grade students at SD Negeri Sidorejo 02. The main objective of this research is to analyze the role of real problem-based learning, active discussions, reflection, and the connection between learning materials and students’ daily lives in improving their ability to understand issues, provide logical reasons, and express opinions rationally. The study employed a descriptive qualitative method involving one fifth-grade teacher and eight students. Data were collected through observations, in-depth interviews, and documentation, and were analyzed using the interactive model of Miles and Huberman as well as NVivo software. The findings indicate that the implementation of Deep Learning is effective in increasing student participation, enhancing their ability to explain concepts in their own words, strengthening their confidence in expressing opinions, and improving their skills in analyzing and evaluating problems in a deeper and more contextual manner.